1999
DOI: 10.1111/1468-5965.00170
|View full text |Cite
|
Sign up to set email alerts
|

The 1992 CAP Reform, the Uruguay Round and the Commission: Conceptualizing Linked Policy Games

Abstract: Over the past decade, most OECD countries have begun to reform fundamentally their agricultural policies. Some dispute has emerged over the extent to which policy-making at the international level has triggered and shaped these reforms. These disputes raise important theoretical questions about how we theorize and test for the degree of interdependence between international, European Union (EU), and domestic policy change. The concept of autonomous, linked games is offered as a possible theoretical route to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 15 publications
0
36
0
1
Order By: Relevance
“…The EU's compensatory payments as well as specific US support schemes ("blue box") were temporarily allowed since they were interpreted as "supports targeting limiting of the production". Investments in rural infrastructure, compensations for specific production practices and other "market non-distorting measures" ("green box") remained unconstrained (Coleman and Tangermann, 1999).…”
Section: Globalization Of Agricultural Welfare Statementioning
confidence: 99%
See 1 more Smart Citation
“…The EU's compensatory payments as well as specific US support schemes ("blue box") were temporarily allowed since they were interpreted as "supports targeting limiting of the production". Investments in rural infrastructure, compensations for specific production practices and other "market non-distorting measures" ("green box") remained unconstrained (Coleman and Tangermann, 1999).…”
Section: Globalization Of Agricultural Welfare Statementioning
confidence: 99%
“…"MacSharry's" reform, decreasing institutional prices and introducing compensatory payments, was commonly related to the GATT Uruguay Round Agreement, regulating agricultural subsidies (URAA) (Coleman and Tangermann, 1999;Moyer and Josling, 2002). The Agenda 2000 reform from 1999, when accession negotiations on the agriculture chapter began, and the Mid-Term Review Reform (2003), agreed just after accession negotiations were concluded, phased-out most of the production based supports and instituted direct payments and program-based rural development supports.…”
Section: Introductionmentioning
confidence: 99%
“…In such games, actors involved in a variety of interactions with different potential outcomes combine their separate games to attain optimum outcomes that would not be achievable under games considered separately. Examples have been extensively explored by Coleman & Tangermann (1998);Coleman & Tangermann, (1999);Just and Netanyahu (2000). The use of game theory to understand the choices available to policy actors -and thereby the means by which successful implementation of policy can be accomplished -has been undertaken by a variety of scholars, (Frisvold and Caswell, 2000;Eleftheriadou and Mylopoulos (2008).…”
Section: Implicating Game Theory?mentioning
confidence: 99%
“…Studies of the internal decision-making processes in the framework of the non-CFSP external relations of the EU were mostly limited to the area of trade policy (Coleman & Tangermann, 1999;Collinson, 1999;Kerremans, 2004;Meunier, 1998Meunier, , 2000Nicolaïdis, 1999;Pattersson, 1997;Pollack, 2003;Young, 2003). Analyzing the internal decisionmaking process with regard to external environmental policies, in contrast, adds some complicating factors to the analysis.…”
Section: Conclusion: Eu Decision-making Regarding Mixed Agreements Asmentioning
confidence: 99%